PEMERTAHANAN DAN PELESTARIAN BAHASA MADURA PADA TEKS PEWARA DALAM ACARA OKTOFEST SMAN 1 BLUTO : PERSPEKTIF SOSIOLINGUISTIK. - Chindy Aulia; ShintaAprilia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The announcer is an important figure in an event because it is in charge of leading the course of the event, the text of the announcer analyzed in this research uses Madurese language which aims to describe the Madurese community in maintaining and preserving the Madurese language through the Madurese language announcer in the oktofest event in Bluto District, Sumenep Regency. This research theoretically uses a sociolinguistic approach. The data collection in this research is in the form of the method of listening and writing. The results of this study indicate that (1) The preservation and preservation of the madurese language can still be preserved through the script of the madurese language narrator at the octofest event, (2) The difficulty of language pronunciation in the script of the madurese language narrator at the octofest event and the effort to regenerate the madurese language narrator in the octofest event.